2016
DOI: 10.4103/0975-962x.179371
|View full text |Cite
|
Sign up to set email alerts
|

Glandular odontogenic cyst: A diagnostic dilemma

Abstract: Glandular odontogenic cyst (GOC) is a rare and uncommon jaw bone cyst of odontogenic origin described in 1987 by Gardener et al. as a distinct entity. It is a cyst having an unpredictable, potentially aggressive behavior, and has the propensity to grow in large size with relatively high recurrence rate. It poses a diagnostic challenge as it can be clinically and histopathologically confused with lateral periodontal cyst, botryoid odontogenic cyst, radicular and residual cysts with mucous metaplasia, and low-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…It may present as a unilocular or multilocular radiolucency, which usually shows well-defined borders [ 20 ]. Occasionally, scalloping of the border may be noted, while root resorption and displacement are not commonly seen [ 3 ]. Radiographically, GOC may resemble lesions like radicular cyst, keratocystic odontogenic tumor, ameloblastoma and central giant cell granuloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may present as a unilocular or multilocular radiolucency, which usually shows well-defined borders [ 20 ]. Occasionally, scalloping of the border may be noted, while root resorption and displacement are not commonly seen [ 3 ]. Radiographically, GOC may resemble lesions like radicular cyst, keratocystic odontogenic tumor, ameloblastoma and central giant cell granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner et al in 1988 suggested the name ‘Glandular Odontogenic Cyst’ because the cyst wall epithelium was odontogenic and contained mucin elements with absence of salivary tissue [ 2 ]. In 1992, GOC was included in the WHO typing of tumors under the term GOC or sialo-odontogenic cyst [ 3 ]. An important feature of this cyst is that its recognition on the basis of clinical and radiographic features is practically impossible, and only histopathological examination allows for a certain diagnosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The odontogenic origin of this cyst has been confirmed by immunohistochemistry. It usually presents as an asymptomatic, slow‐growing mass in anterior segment of mandible and is seen mostly among the middle‐aged individuals with a slight increased predilection for males …”
Section: Introductionmentioning
confidence: 99%
“…It usually presents as an asymptomatic, slow-growing mass in anterior segment of mandible and is seen mostly among the middle-aged individuals with a slight increased predilection for males. 3,4 Radiologically, the lesion may appear unilocular or multilocular with defined borders which occasionally may show loss of cortical integrity and root resorption. 5 Histologically, it is characterized by variable thickness of nonkeratinized epithelium consisting of superficial layer of cuboidal or columnar cells that are referred as hobnail cells, and occasionally, these cells may be ciliated.…”
Section: Introductionmentioning
confidence: 99%
“…It was first discussed at the meeting of the International Association of Oral Pathologists in 1984, but was first documented as "sialo-odontogenic cyst" by Padayachee and Van Wyk [3] in 1987. Histologically, in 1988, Gardner et al [4] found that the epithelial lining of this cyst was odontogenic in nature and gave the term "glandular odontogenic cyst," which was later adopted by World Health Organization [5][6][7][8]. Glandular odontogenic cyst is a clinically aggressive lesion that usually requires more radical surgery and longer follow-up than radicular and dentigerous cysts [9].…”
Section: Introductionmentioning
confidence: 99%